Stimulated Biodegradation of Used Lubricating Oil in Soil Using Organic Wastes - O. P, Abioye; A, Abdul Aziz; P, Agamuthu (Malaysian Journal of Science, 2009)
Biostimulation studies of soil contaminated with used lubricating oil was undertaken with three organic wastes (Banana skin BS, Brewery spent grain BSG and Spent mushroom compost SMC) used as sources of nutrient to enhance biodegradation of used lubricating oil in soil for a period of 84 days under laboratory conditions. The hydrocarbon loss in the soil shows positive linear correlation with evolution of CO2 in the soil. 42.05% oil loss was recorded in the unamended polluted soil while 68.73%, 62.03% and 57.01% oil loss were recorded in soil amended with BSG, BS and SMC respectively in 84 days. Hydrocarbon utilizing bacterial (HUB) counts were high in all the organic wastes amended soil ranging between 10.2 x 106 CFU/g of soil to 80.5 x 106 CFU/g of soil compared to unamended control soil (1.0 x 106 CFU/g to 3.5 x 106 CFU/g of soil) throughout the 84 days of study. The counts in amended soil was significantly different at (P<0.05) from the unamended polluted soil. The HUB was identified as species of Acinetobacter, Nocardia, Pseudomonas, Micrococcus and Bacillus. The results obtained demonstrated the potential of BSG, BS and SMC for enhanced bioremediation of hydrocarbon contaminated soil.